The Crank–Nicolson–Galerkin Finite Element Method for a Nonlocal Parabolic Equation with Moving Boundaries - Almeida, Rui M.P. (2020)
The aim of this article is to establish the convergence and error bounds for the fully discrete solutions of a class of nonlinear equations of reaction–diffusion nonlocal type with moving boundaries, using a linearized Crank–Nicolson–Galerkin finite element method with polynomial approximations of any degree. A coordinate transformation which fixes the boundaries is used. Some numerical tests to compare our Matlab code with some existing moving finite element methods are investigated.